2020
DOI: 10.1002/ece3.6299
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific comparison of the fecal microbiota structure in three Arctic migratory bird species

Abstract: The gut microbiota of birds is known to be characterized for different species, although it may change with feeding items. In this study, we compared the gut microbiota of birds with different feeding behaviors in the same habitat. We collected fecal samples from three Arctic species, snow buntings Plectrophenax nivalis, sanderlings Calidris alba, and pink‐footed geese Anser brachyrhynchus that are phylogenetically quite distant in different families to evaluate effects of diet on gut microbiota. Also, we char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…In recent years, in order to better understand the interactions between gut microbes and their hosts, studies of gut microbes conducted on singlespecies or multi-species host have been carried out in many animal groups including mammals (Lu et al, 2012;Russell et al, 2012;Tung et al, 2015;Davis M. Y. et al, 2016;de Goffau et al, 2019;Xiao et al, 2019), birds (Ding et al, 2016(Ding et al, , 2020Grond et al, 2017), reptiles (Ren et al, 2016;Kohl et al, 2017), and fish (Davis D. J. et al, 2016). Studies on avian gut microbiota have increased rapidly since 2014 (Hird et al, 2015;Kohl et al, 2018;Wang et al, 2019b;Capunitan et al, 2020;Cho and Lee, 2020;Song et al, 2020), remain heavily outnumbered by studies of mammals, and are dominated by research on domestic poultry (Cui et al, 2017) or captive-bred model species (Ding et al, 2020). Therefore, wild birds remain understudied despite their relevance for pathogen transmission and for understanding diet and environmental influences on gut microbial structure and function.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, in order to better understand the interactions between gut microbes and their hosts, studies of gut microbes conducted on singlespecies or multi-species host have been carried out in many animal groups including mammals (Lu et al, 2012;Russell et al, 2012;Tung et al, 2015;Davis M. Y. et al, 2016;de Goffau et al, 2019;Xiao et al, 2019), birds (Ding et al, 2016(Ding et al, , 2020Grond et al, 2017), reptiles (Ren et al, 2016;Kohl et al, 2017), and fish (Davis D. J. et al, 2016). Studies on avian gut microbiota have increased rapidly since 2014 (Hird et al, 2015;Kohl et al, 2018;Wang et al, 2019b;Capunitan et al, 2020;Cho and Lee, 2020;Song et al, 2020), remain heavily outnumbered by studies of mammals, and are dominated by research on domestic poultry (Cui et al, 2017) or captive-bred model species (Ding et al, 2020). Therefore, wild birds remain understudied despite their relevance for pathogen transmission and for understanding diet and environmental influences on gut microbial structure and function.…”
Section: Introductionmentioning
confidence: 99%
“…We synthesized published 16S rRNA gene data (Table 1, 506 samples using high-throughput sequencing technology) in the migratory shorebirds (Cho & Lee, 2020;Grond et al, 2019Grond et al, , 2020Risely et al, 2017Risely et al, , 2018 and found the predominant phyla of these 13 shorebird species include Firmicutes, Bacteroidetes, Proteobacteria, Fusobacteria, and Actinobacteria (Figure 1). Firmicutes is also a dominant phylum in the other seven migratory shorebirds (Table 1): Clone sequencing: Himantopus himantopus, Limosa limosa, and Tringa totanus (Santos et al, 2012); clone sequencing: Arenaria interpres, Calidris canutus, and Calidris pusilla (Ryu et al, 2014); one sample: Actitis hypoleucos (Capunitan et al, 2020).…”
Section: Corynebac Terium Enriched In the G Ut MI Crob I Ome Of The Recently Arrived Mig R Atory S Horeb Irds P Otentially Rel Ated To Thmentioning
confidence: 99%
“…Social contact among intraspecies and interspecies may lead to the gut microbiome transmission and affect the gut bacterial communities in individual animals (Antwis et al, 2018;Archie & Tung, 2015;Grond et al, 2014;Kwong & Moran, 2016;Ryu et al, 2014). Different species of migratory shorebirds have direct or indirect contact because they share habitat and food during their migrations or breeding (Cho & Lee, 2020;Grond et al, 2019;Risely et al, 2017Risely et al, , 2018Ryu et al, 2014;Santos et al, 2012). Therefore, we speculated that the effects of social contact on the gut microbiome community of the migratory shorebirds might also modify the effects contributed by host phylogeny.…”
Section: Hos T Phylog Eny and P Otential So Cial Contac T Affec Ting The G Ut MI Crob I Ome Communit Y Of The Mig R Atory S Horeb Irds Dumentioning
confidence: 99%
See 1 more Smart Citation
“…Fig 28. Relative abundances of dominant bacterial phyla in the faeces of three arctic birds (B4, B5, B6, B9-Snow bunting; S1, S2, S3, S5, S6-Sanderling; P1, P2, P3, P4, P6-Pink-footed goose).…”
mentioning
confidence: 99%